Effect of Zirconia Dental Implant Surfaces on Bone Integration: A Systematic Review and Meta-Analysis - Hafezeqoran, Ali (Biomed Res Int, 2017)
Background. The information available about osseointegration and the bone to implant interaction of zirconia implants with various surface modifications is still far from sufficient. Objective. The purpose of this systematic review and meta-analysis was to evaluate and compare zirconia dental implants with different surface topographies, with a focus on bone to implant contact and removal torque. Methods. The systematic review of the extracted publications was performed to compare the bone to implant contact (BIC) with removal torque (RT) values of titanium dental implants and machined and surfaced modified zirconia implants. Results. A total of fifteen articles on BIC and RT values were included in the quantitative analysis. No significant difference in the BIC values was observed between titanium and machined zirconia implants (p = 0.373; 95% CI: −0.166 to 0.443). However, a significantly better BIC values were observed for acid etched zirconia implants compared with those of titanium implants (p = 0.032; 95% CI: 0.068 to 1.461). Unmodified zirconia implants showed favorable BIC values compared to modified-surface zirconia implants (p = 0.021; 95% CI: −0.973 to −0.080). Conclusion. Acid etched zirconia implants may serve as a possible substitute for successful osseointegration.